Strengthening Community Engagement in Local Disaster Management: The Northern Mindanao, Philippines Experience - Pasamonte, Rona Celeste Valledor (Journal Public Policy, 2025)
Community engagement plays a crucial role in effective disaster management at the local level. As a representative voice of the citizens, civil society has worked alongside the government to broaden service delivery and act as collaborators in developing programs tailored to the community's needs. This study examines the engagement of Civil Society Organizations (CSOs) in the local disaster risk reduction management council (LDRRMC) of Bukidnon Province, Northern Mindanao, Philippines. Employing a descriptive-quantitative approach, the research evaluates CSOs' involvement in the functional areas of planning, budgeting, implementation monitoring, and evaluation, utilizing a structured survey among CSOs and local government units (LGUs). The results indicated that the CSOs were most engaged in the planning stage while least engaged in the monitoring and evaluation. The findings highlight the need for clear guidelines and capacity development to enhance CSO engagement. Global practices from countries like Japan, South Korea, and India underscore the importance of participatory and network governance to strengthen collaboration. This study contributes to the growing body of literature on CSO participation in disaster governance.